The Key Factors of Watching Live Streaming in Taiwanese Manufacturing Sectors Identified by the Analytic Hierarchy Process - Thi-Them Hoang; Yung-Fu Huang; Manh-Hoang Do (Engineering Proceedings)
Live streaming has become an emerging business with a firm performance. We investigated the key factors that attract audiences to watch live streaming in the Taiwanese manufacturing industry. Nine experts in manufacturing and social media marketing participated in this study. The analytic hierarchy process (AHP) was employed to evaluate the key factors. Three main determinants were determined as a result, including audience motivation, pricing, and branding, each of which was further divided into three sub-factors. Consequently, the results revealed that the most essential factors of these three clusters were social aspects, brand design, and business trend analysis. The results also allow for an understanding of how traditional manufacturers have utilized live streaming to promote products and engage with their audience. These findings serve as a reference for Taiwanese manufacturers to incorporate live streaming into their business promotion strategies.